PELATIHAN PEMBUDIDAYAAN DAN PENGOLAHAN ALOE VERA MENJADI MAKANAN DAN MINUMAN YANG LEZAT, BERGIZI DAN KAYA MANFAAT UNTUK MENDONGKRAK PEREKONOMIAN MASYARAKAT DI DESA PUNGE BLANG CUT KECAMATAN JAYA BARU KOTA BANDA ACEH - Monawati Monawati; Indani Indani; Rosma Elly (Jurnal Pesona Dasar, 2021)
One of the villages located in the Jaya Baru District of Banda Aceh City is the village of Punge Blang Cut which has five hamlets. Two of them are Tuan Dikandang and Tuan Dipakeh. Dusun Tuan Dikandang has 1 faqir community and 28 poor people. This faqir / poor community education is: no school 5 people, elementary school: 7 people, junior high school: 9 people, and high school: 8 people. Their jobs are housewives: 14 people, entrepreneurs: 3 people, not / haven't worked: 7 people, tire patchers: 1 person, 3 builders, and becak drivers: 1 person. Hamlet Tuan Dipakeh faqir community 3 people and 44 people poor. Their education is not in school: 1 person, elementary school: 2 people, junior high school: 14 people, high school: 25 people, D III: 2 people, and S1: 3 people. Their work is tricycles: 3 people, IRT: 6 people, entrepreneurs: 16 people, selling stalls: 4 people, making cakes: 3 people, unskilled laborers: 6 people, drivers: 3 people, not working: 3 people, and each - 1 person cut grass, sells fruit and a docker. Aloe Vera is one of the ten types of best-selling plants in the world that have the potential to be developed as medicinal plants and industrial raw materials that can be used both in the world of beauty and food that has many benefits. The purpose of this Community Service is to make training and cultivation of Aloe Vera and process it into healthy, nutritious food and many benefits, as well as business opportunities in order to improve the economy of the people in the two hamlets. The method of conducting training in processing Aloe Vera is an explanation by demonstration / practice of discussion and question and answer as well as how to cultivate Aloe Vera. All participants were distributed modules, tools and materials needed. The training activities are guided by resource persons who are competent in their bidag. The target to be achieved is 30 mothers / fathers who are skilled in cultivating Aloe Vera, and 30 mothers / fathers who are skilled in processing Aloe Vera into delicious, nutritious and rich food.